Knowledge, attitude, and practices assessment of menstrual cycle and management of menstrual hygiene among adolescent girls - Nelapati, Sherly S. (International Journal Of Community Medicine And Public Health, 2022)
Background: Menstruation is a phenomenon which is cyclic shedding of endometrium and is the most important physical change that occurs among girls during adolescence. In India, lack of safe sanitary facilities and narrow approach to products of sanitary hygiene lead to increase in adopting unhygienic practices in managing menstruation. The objectives of this study were: to enumerate the common menstrual morbidities among girls; to study the knowledge and attitude toward menstruation among adolescent girls; to elicit their health‑seeking behavior regarding menstrual health; and to study the practices of menstrual hygiene among adolescent girls. Methods: A cross-sectional study was conducted in a tertiary care hospital, located in Vijaywada, June 2019 to April 2020 by interviewing 417 adolescent school girls in using a semi‑structured questionnaire. Results: The mean age and standard deviation of girls included in the study were 14.7±2.69 years. 62.6% girls had the right perception about menstruation as a normal physiological process. Only 33.6% of girls knew about menstruation before menarche. 32% of girls answered that they were scared when they attained first menarche. 50.6% girls knew that infection would occur if they do not clean their vagina regularly during menstruation.78% of girls used sanitary pads during menstruation. Dysmenorrhea, 58% is the common menstrual morbidity. Only 11% girls said that they had no restrictions during menstruation. Conclusions: The girls interviewed, are of unsatisfactory knowledge and markable good practices regarding menstrual health.